Individual, Group Dynamics, and Organizational Processes in the Workplace: Factors for Better Performance and Organizational Success - Moh. Saiful Hakiki; Dwi Aprilia Anggraini; Norma Farizah Fahmi; Riyan Sisiawan Putra; Mukhtar Adinugroho (Journal on Education, 2023)
Introduction/Main Objectives: Research in individual, group dynamics, and organizational processes for organizational behavior can offer valuable insights into how people behave in the workplace. These insights can assist organizations in enhancing their effectiveness, promoting teamwork, and cultivating a culture that is more diverse and inclusive. Background Problems: Organizational behavior is complex and multifaceted, and there are many different factors that can influence good work performance. Novelty: In the area of organizational behavior, there is a growing interest in the intersection of technology and human behavior, also the need to understand team performance and collaboration. There is a lot of need to explore literature studies in various time spans regarding these aspects to be able to find models related to new systems and technologies. Research Methods: Literature study, a research method that involves collecting and analyzing existing research and academic literature on this topic. The data in this study are from previous studies in the form of textbooks, research papers, and articles. Research was conducted with 6 steps of literature study. Finding/Results: There are 7 main factors and 18 sub factors related to individual aspects. There are 6 main factors and 18 sub factors related to group aspects. And there are 3 main factors and 9 sub factors related to organizational processes, where the three main factors above affect good work performances. Research results can be further tested in specific organizational environments for the development of knowledge and to explain empirical and theoretical gaps.